Understanding the Role of the Public Employment Agency - Christian Holzner; Makoto Watanabe (Tinbergen Institute, 2016)
Using a unique vacancy dataset, we find that the Public Employment Agency (PEA) distributes workers more evenly across vacancies than the private market. We investigate the implications of having such a market place by using a directed search model, where firms can search via the PEA or the private market. Lower coordination frictions reduce wage competition and enable registered firms to pay lower wages compared to the private market. This advantage has to be traded off against the negative selection of applicants coming through the PEA. We take these theoretical predictions to the data and find strong support for them.
Keywords: J6; 330; Labor Search; Intermediation; Public Employment Agency